The 5'-flanking sequence of human interferon-beta 1 gene is responsible for viral induction of transcription. - Ohno, S (1983)
The structural gene for Herpes simplex virus (HSV) thymidine kinase (Tk) was fused downstream of the 5'-flanking sequence (from -284 to +20; numbering relative to the putative transcription initiation site) of the cloned human interferon-beta 1 (IFN-beta 1) gene. The fusion gene was linked to the vector pSV2-Ecogpt and the recombinant plasmid was used to transform mouse FM3A cells. All cloned transformants in which the fusion gene was integrated in an intact form produced the Tk specific transcript with the distinct 5' terminus corresponding to that of the authentic IFN-beta 1 mRNA when they were exposed to Newcastle disease virus (NDV). Thus, the results reported here provide evidence for the presence of specific DNA sequences in the 5'-flanking region of the IFN-beta 1 gene required for the virus mediated activation of transcription.